Photoresponsive Foams Generated by a Rigid Surfactant Derived from Dehydroabietic Acid - Lei, Lan (Langmuir : the ACS journal of surfaces and colloids, 2017)
Innovation in the structure of surfactants is crucial to the construction of a surfactant-based system with intriguing properties. With dehydroabietic acid as a starting material, a nearly totally rigid azobenzene surfactant (R-azo-Na) was synthesized. The trans-R-azo-Na formed stable foams with half-lives of 636, 656, 976, and 872 min for 0.3, 1, 2, and 4 mmol·L-1 aqueous solutions, respectively. Under UV light irradiation, a fast collapse of the foams was observed, showing an in situ response. The excellent foam stability of trans-R-azo-Na leads to the extremely high photoresponsive efficiency. As revealed by dynamic surface tension and pulsed-field gradient NMR methods, an obvious energy barrier existed in the adsorption/desorption process of trans-R-azo-Na on the air/water interface. The foams formed by trans-R-azo-Na are thus stable against coarsening processes. The results reveal the unique photoresponsive behavior of a surfactant with a rigid hydrophobic skeleton and provide new insights into the structure causing aggregation of surfactants